2023
DOI: 10.1021/acsami.3c05236
|View full text |Cite
|
Sign up to set email alerts
|

Control of Intermolecular Interactions toward the Production of Free-Standing Interfacial Polydopamine Films

Abstract: Aggregation of the polydopamine (PDA) molecular building blocks at the air/water interface leads to obtaining large surface nanometric-thin films. This mechanism follows two possible pathways, namely, covalent or non-covalent self-assembly, which result in a different degree of structure order and, consequently, different structural properties. Control of this mechanism could be vital for applications that require true self-support PDA free-standing films, for example, electrochemical sensing or membrane techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…In turn, the CHX immobilization on the pDA film caused a modest increment of surface roughness, as illustrated in Figure A. It has been recently reported that the mechanical properties of pDA films can be coordinated by the addition of new molecules . Previous findings demonstrated the higher surface roughness on CHX coatings due to the occurrence of CHX aggregates and several protrusions on the grafted pDA layer .…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In turn, the CHX immobilization on the pDA film caused a modest increment of surface roughness, as illustrated in Figure A. It has been recently reported that the mechanical properties of pDA films can be coordinated by the addition of new molecules . Previous findings demonstrated the higher surface roughness on CHX coatings due to the occurrence of CHX aggregates and several protrusions on the grafted pDA layer .…”
Section: Resultsmentioning
confidence: 77%
“…The lack of an unambiguous pDA structure and clear mechanistic studies driving its formation make the understanding of its interaction with other molecules very complex and speculative. Due to the very nature of the functionalization process, involving the immersion of samples in antimicrobial solutions for long periods (∼18 h), it is mostly expected that favorable physical (noncovalent) adsorption/interaction occurs either by interference in the network of hydrogen (H) bonding between chains or involving π–π stacking, van der Waals forces, and hydrophobic interactions. , Therefore, this approach will lead to the development of a release system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It most likely indicates the coordination of nitrogen to titanium atoms on the TiO 2 surface. , This is particularly reasonable because PDA adheres to surfaces via catechol and amino groups containing nitrogen. The peaks N2 and N3 cannot be assigned with certainty because they overlap with peaks typical for PDA (primary and secondary amine groups), which are also visible for shorter etching times (Figures S1 and S2). However, it is visible that the intensity of N1 increases with an increasing etching time.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We have previously shown that PDA free-standing films produced at the air/water interface (a/w-PDA) are characterized by a 2D-like laminar structure, 14 which can be obtained on a large scale (up to several cm) while maintaining homogeneity and continuity, 15 and are easily transferable to any desired substrate due to their extraordinary mechanical properties. 16 Ex situ transferred PDA is a thin layer of PDA that is free-standing on the water surface and can be transferred to another desired surface. Such nanometrically thin a/w-PDA films transferred ex situ to the surfaces of semiconductors (ZnO and TiO 2 ) can create efficient and stable heterojunctions useful in photocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%